2016
DOI: 10.1016/j.scitotenv.2016.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Household concentrations and personal exposure of PM2.5 among urban residents using different cooking fuels

Abstract: Exposure to PM2.5 is a leading environmental risk factor for many diseases and premature deaths, arousing growing public concerns. In this study, indoor and outdoor PM2.5 concentrations were investigated during the heating and non-heating seasons in an urban area in northwest China. Personal inhalation exposure levels among different age groups were evaluated, and the difference attributable to different cooking fuels including coal, gas and electricity, were discussed. The average concentrations of PM2.5 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 30 publications
0
45
4
2
Order By: Relevance
“…Compared to natural gas, kerosene/diesel and solid fuel burning are associated with higher indoor PM 2.5 and polyaromatic hydrocarbon concentrations, 33-35 which could contribute to downstream adverse health consequences including the observed increases in all-cause and CVD mortality seen in the present study. Insufficient exposure times to solid fuel burning in the present study could explain the lack of an observed effect on mortality.…”
Section: Discussionmentioning
confidence: 65%
“…Compared to natural gas, kerosene/diesel and solid fuel burning are associated with higher indoor PM 2.5 and polyaromatic hydrocarbon concentrations, 33-35 which could contribute to downstream adverse health consequences including the observed increases in all-cause and CVD mortality seen in the present study. Insufficient exposure times to solid fuel burning in the present study could explain the lack of an observed effect on mortality.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, the underlying mechanisms involved in the pathogenesis of diabetes may be related to the induction of oxidative stress and inflammation in the lungs, representing releases of pro‐inflammatory cytokines (such as TNF‐a and IL‐6) and chemokines (such as CCL‐5) . Evidence has shown that more than 75% of the overall PM 2.5 exposure occurred indoors in females aged ≥15 years, and exposure to indoor PM 2.5 was positively associated with FeNO level . The results indicated that the cooking individuals with liquefied petroleum gas used for cooking had a relative increase of 5.75% (95% CI: 0.10%‐11.73%) in FeNO compared with those with natural gas used for cooking .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and Duan [ 80 ] showed that burning a mosquito coil ring could release 626 μg·m −3 of PM 2.5 , which is 8.3 times the concentration limit allowed for the residential environment. Li et al [ 81 ] concluded that PM 2.5 concentration in households using coal to cook was significantly higher than those using gas or electricity, and if coal is switched to gas or electricity, the PM 2.5 concentration in the kitchen could be reduced by 40–70%. Zhou et al [ 82 ] indicated that human activities such as walking, dressing and cleaning could result in increased indoor PM 2.5 concentration by 33%.…”
Section: Sources Of Pm 25mentioning
confidence: 99%